Systematic review of Kaixinsan in treating depression: Efficacy and pharmacological mechanisms - Bo, Menghan; Zhang, Hongjing; Xu, Jia; Zhao, Hong; Jia, Xinglei; Wang, Guangdong; Lu, Zhengyu (Frontiers in Behavioral Neuroscience, 2022)
Abstract Kaixinsan (KXS) has been in use as an effective classic formulation of traditional Chinese medicine for depression. However, its active components and action mechanism against depression remain elusive. The purpose of this study was to evaluate the efficacy and potential pharmacological mechanisms of KXS as an antidepressant. Reports on the use of KXS in the treatment of depression were systematically collected from PubMed, Web of Science, Embase, China National Knowledge Infrastructure, Chongqing VIP, and Wanfang Data from the establishment to July 2022, including those on mood disorders in neurological diseases such as Alzheimer’s disease. Meta-analysis was conducted with the Review Manager 5.3 software. Online datasets, traditional Chinese medicine system pharmacological analysis platform, GeneCards, online Mendelian inheritance in man, and DisGeNET were used to investigate the depression-related genes. The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichments were performed to construct the ‘component-target-pathways’ network using Metascape online analyses. Ten studies were included in the analysis. Meta-analysis showed that both low-dose KXS (SMD = 19.66, Z = 7.96, I2 = 42%) and high-dose KXS (SMD = 23.84, Z = 8.46, I2 = 13%) could increase the sucrose preference in depression models. In addition, 5-hydroxytryptamine (5-HT) (SMD = 10.91, Z = 2.95, I2 = 50%) returned to normal level after the treatment at low dose KXS. In network pharmacology, 50 active components and 376 gene targets were screened out. AKT1, GAPDH, ALB, TNF, and TP53 were the core target proteins. GO analysis showed that KXS mainly treats depression in biological processes such as response to drugs, cellular calcium ion homeostasis, and regulation of chemical synaptic signal transmission. KEGG results show that the mechanism of action of KXS in treating depression is through neural activity ligand-receptor interaction, the calcium signaling and CAMP signaling pathways. The study reveals the active components and potential molecular mechanism of KXS in the treatment of depression and provides evidence for future basic research.